Assessment of proximate composition and tetrodotoxin content in the muscle of Yellow puffer fish, Xenopterus naritus (Richardson 1848) from Sarawak, Malaysia - Mohd Nor Azman, A.; Samsur, M.; Mohammed, M.; Shabdin, M.L.; Fasihuddin Badruddin, Ahmad (IFRJ Publisher, 2015)
This study is to report the proximate compositions as well as tetrodotoxin (TTX) content in the muscles of yellow puffer fish Xenopterus naritus that collected from Kg. Manggut and Kabong, Sarawak. The internal organs of 26 and 20 specimens from Kg. Manggut and Kabong respectively were removed by the local people that had skills and experiences with the preparation of yellow puffer fish. In general, the moisture contents were ranging between 75.2% and 80.6%. X. naritus from Kabong showed higher crude protein contents (88.2% dry weight) than the same species from Kg. Manggut (87.9% dry weight) and not significantly different (p>0.05). X. naritus from Kg. Manggut demonstrated a significantly higher (p<0.05) of crude fat contents (0.49% dry weight), crude fibre contents (0.44% dry weight) and ash contents (5.48% dry weight) compared to X. naritus from Kabong which were 0.47%, 0.25% and 5.08% dry weight respectively. The TTX content in the muscle of X. naritus that prepared by the unskilled person from Kg. Manggut showed significantly higher (65.3 μg/g) (p<0.05) than X. naritus that prepared by the skilled person from Kabong (6.63 μg/g) and found to be toxic for human consumption (>2 μg/g) based on Japanese regulation as Malaysia does not have the regulatory limits for TTX yet. Nevertheless, it can be consumed safely if prepared in a proper manner. This is the first report to determine the proximate composition from the muscle of yellow puffer fish from Sarawak. The proximate values obtained from this study shows that the yellow puffer fish X. naritus are good protein resources. Therefore, it can be considered for human consumption in countries. The information gained from this study indicates the importance removing TTX to ensure the safe consumption of puffer fish.